(untitled) (Journal of Plant Disease Sciences, 2025)
Marigold (Tagetes spp.) is an important traditional flower crop widely cultivated across India, particularly in South Gujarat. Despite its commercial significance, its productivity is severely affected by leaf spot and flower blight caused by Alternaria tenuissima. This study focused on biochemical changes occurring in one resistant variety (Gulzafri Yellow) and one susceptible variety (Punjab Gainda) of marigold following infection. The biochemical parameters analyzed included: